The Influence of Price, Marketing Strategy, and Creativity on Purchase Decisions at PT. Terbit Terang Medan - Cindy Eka Rivanni; Andi Susanto Zamili; Debora Intan Yosephine; Rosinta Romauli Situmeang (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of price, marketing strategy, and creativity on purchasing decisions at PT. Terbit Terang Medan. Data collection using a questionnaire, multiple linear regression analysis models. The study results show that price, marketing strategy, and creativity affect purchasing decisions at PT. Terbit Terang Medan with a coefficient of determination R square 0.547. Price partially influences purchasing decisions with a coefficient value of 0.710; Marketing Strategy partially affects 0.038, creativity partially affects purchasing decisions with a coefficient value of 0.282, The dominant factor influencing purchasing decisions is price.